RESEARCH OF LASER THERMOHARDENING PROCESSES ОF INTERNAL CONTACT SURFACES IN TRACTOR «BELARUS» BRAKE MECHANISMS - O. S. Kobiakov; N. V. Spiridonov; M. A. Kardapalova; A. A. Barkun (Наука и техника)
The paper contains research pertaining to laser thermohardening processes of high-strength ВЧ-50 cast iron and grey СЧ-20 cast iron with reference to a problem concerning an increase of wear resistance and operational properties of tractor «Belarus» brake mechanisms.